Strategi Sustainable Business Model Innovation pada Industri Fashion Digital Ilustrasi - Berliandika, Beata; Isfianadewi, Dessy; Priyono, Anjar (Jurnal Samudra Ekonomi dan Bisnis, 2022)
The fashion business is an industry that continues to grow due to the high demand for these products, but has weaknesses in terms of environmental sustainability so it is necessary to apply the concept of Sustainable Business Model Innovation (SBMI). The purpose of this study is to identify SBMI strategies in the digital fashion industry in increasing consumer behavior and awareness of domestic products and environmentally friendly products. This study uses a descriptive qualitative method with triangulation data collection methods obtained from a case study at the Pijar Benderang company as an actor of illustration digital fashion business. The findings obtained are that it is necessary to create business storylines and concepts offered to increase sales, conduct a pre-order system to reduce waste, use eco-friendly materials, carry out social and environmental activities, and maximize online sales activities.